Identification of a molecular gating determinant within the carboxy terminal region of Cav3.3 T-type channels - Jurkovicova-Tarabova, Bohumila; Cmarko, Leos; Rehak, Renata; Zamponi, Gerald W; Lacinova, Lubica; Weiss, Norbert (Molecular brain, 2019)
The physiological functions controlled by T-type channels are intrinsically dependent on their gating properties, and alteration of T-type channel activity is linked to several human disorders. Therefore, it is essential to develop a clear understanding of the structural determinants responsible for the unique gating features of T-type channels. Here, we have investigated the specific role of the carboxy terminal region by creating a series a deletion constructs expressed in tsA-201 cells and analyzing them by patch clamp electrophysiology. Our data reveal that the proximal region of the carboxy terminus contains a structural determinant essential for shaping several gating aspects of Cav3.3 channels, including voltage-dependence of activation and inactivation, inactivation kinetics, and coupling between the voltage sensing and the pore opening of the channel. Altogether, our data are consistent with a model in which the carboxy terminus stabilizes the channel in a closed state.
Keywords: Cav3.3 channel; Electrophysiology; Calcium Channels, T-Type; sekvence aminokyselin; Structure-Activity Relationship; T-type channels; lidé; Kinetics; vztahy mezi strukturou a aktivitou; HEK293 buňky; gating iontového kanálu; vápníkové kanály - typ T; Humans; Ion Channel Gating; Amino Acid Sequence; Gating; HEK293 Cells; kinetika